(3TQM GddeYIs - (3eMeO GdNVQi GdTGYais; (3Gdche GdQjTj , CMeO Hf ZdGe Gddg Hf CMeO Hf eMeO, TgGH GdOjf,J (B836 (3g` s ((3eMeO GdNVQi s)
(3ChdgG (B:s
(3HYO GdOjHGLI (B: (3Efg deG cGf GdGTJZGd Haf GdejbGJ ef CTQa eG JUQa ajg GdBYeGQ hGdChbGJ s
(3BNQgG (B:s
(3agh jYRh hjZdh hjQJaY hGdGfYcGSg aGfXQ Pdc ai cJH GdCMcGe hgPG BNQ eG jSQg Gddg s
(3GddeYI jSei (B" (3GddeYI ai Md GdSHYI(B"s
(3GdfGSN fbdI ef GdeShOIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3Gdadcs